MENDESKRIPSIKAN ANALISIS NILAI KARAKTER ISLAM DALAM MEMBENTUK SELF-REFLECTION PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH BANGKA BELITUNG - Tohir, Muhamad (ANDRAGOGI, 2023)
This research is motivated by the low level of student self-reflection in reflecting on Islamic habits when it is time for prayer, but some students don't pay attention. This study aims to make self-reflection of students at Muhammadiyah University of Bangka Belitung. Islamic Religious Education has an important role in developing student character values. The location of this research is located in Unmuh Babel. Islamic religious education also encourages students to obey religious teachings and make religion the foundation. Islamic religious education is essentially a building of the nation's moral values. The type of this research is descriptive qualitative. The subjects in this study were students of PGSD, PMTK, Computer Science, Civil Engineering. The data collection techniques used were observation, questionnaires and interviews. This research will also interview one of the Al Islam lecturers at Unmuh Babel. This research gives the result that students find it difficult to self-reflect in instilling Islamic character values. Based on the research results, instilling character values ​​in the Babel community can be designed and practiced in the learning process by integrating the 5 Islamic values ​​that exist in the Babel community. This research hopes that students will not only understand theories, but also be able to apply these Islamic values ​​in their daily lives so that this can shape their identity or reflect their personality for the better.